Police Interrogation of Juveniles: An Empirical Study of Policy and Practice - Feld, Barry C (2006)
The Supreme Court does not require any special procedural safeguards when police interrogate youths and use the adult standard--“knowing, intelligent, and voluntary under the totality of the circumstances”--to gauge the validity of juveniles' waivers of Miranda rights. Developmental psychologists have studied adolescents' capacity to exercise Miranda rights, questioned whether juveniles possess the cognitive ability and adjudicative competence necessary to exercise legal rights, and contended that immaturity and vulnerability make juveniles uniquely susceptible to police interrogation tactics. In the four decades since the Court decided Miranda, we have almost no empirical research about what actually occurs when police interview criminal suspects, and we have no research about how police routinely question delinquents. Since 1994, the Minnesota Supreme Court has required police to record all interrogations of criminal suspects, including juveniles. This Article begins to fill the empirical void about adolescents' competence in the interrogation room. It analyzes quantitative and qualitative data-- interrogation tapes and transcripts, police reports, juvenile court filings, and probation and sentencing reports--of routine police interrogation of fifty-three juveniles sixteen years of age or older and charged with felony-level offenses who waived their Miranda rights. It provides the first empirical analyses of the tactics and techniques police use to interrogate juveniles and how youths respond to them. Based on the data analyses, the Article addresses three interrogation policy issues: mandatory recording; limiting the lengths of interrogation; and the use of false evidence to elicit confessions